BUSINESS STRATEGY TO MAXIMIZE NON-AERONAUTICAL REVENUE FROM RETAIL BUSINESS CASE STUDY: SOEKARNO – HATTA INTERNATIONAL AIRPORT (The Indonesian Journal of Business Administration, 2019)
Soekarno Hatta International Airport concessions and rental income must be increased by strong retail performance trough managing the shopping experience of passengers as well as collaboration between concessionaires, airports, and airlines. The proposed strategy is derived from Porter’s Generic Strategy that Soekarno Hatta International Airport in retail business should implemented the integrated cost leadership and differentiation strategy to control the prices but still maintaining the quality of the services, and TOWS matrix analysis are used to define the appropriate strategy and developing the capabilities and core competencies of retail business development to keep sustaining in the retail business at airport.The implementation in this final project will guide company to reach the target portion of non-aeronautical revenue. PT Angkasa Pura II's non-aeronautical revenue maximum target plan by implementing the strategy is IDR3,965,478,878 that represents 52% of PT Angkasa Pura II's non-aeronautical revenue in the coming years with the composition of contributing revenue from retail business in Soekarno Hatta International Airport approximately IDR815.581.726 by the end of 2023.Keywords: Airport, Business strategy, Non-aeronautical revenue, Retail business